ANALISIS KEMAMPUAN LITERASI MEMBACA SISWA KELAS 1 DI MI MANBA'UL ULUM TUBAN - Arantisi, Arjuna; Indah Herawat, Isti; Agustin Ningsih, Widji; Kamilah, Arina; Ika Deviyana, Nova; Dina Hafni, Nurlaili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading literacy skills in early grade elementary students remain an essential foundation for supporting overall learning success; however, many students are still able to read fluently without fully understanding the content of the texts they read. This study aims to analyze the reading literacy skills of first-grade students at MI Manba’ul Ulum Tuban, including the level of students’ reading ability, teaching methods used by teachers, difficulties faced by students, as well as teachers’ efforts and parental involvement in supporting reading development. This research employed a qualitative descriptive approach involving classroom teachers and first-grade students as research subjects. Data were collected through observation, interviews, and documentation techniques, and analyzed using data reduction, data display, and conclusion drawing procedures. The results showed that most students were able to read simple words and sentences fluently, although their reading comprehension ability was still limited. Teachers applied various instructional methods such as listening-reading activities, shared reading, and learning through play supported by picture media. The main difficulty experienced by students was low motivation and reading interest. Teachers addressed these challenges by providing additional individual assistance and conducting continuous evaluation during each learning session. Furthermore, parental involvement at home played an important role in supporting students’ reading literacy development.